Probiotic-Based Optimization of Pistachio Paste Production and Detoxification of Aflatoxin B1 Using Bifidobacterium lactis - Mehdi Pakizeh; Leila Nouri; Mohammad Hossein Azizi (Journal of Food Quality)
Pistachio paste is very popular for breakfast or supper thanks to its desirable taste, flavor, and texture. One of the hazards that are directly related to agricultural practices, processing, storage, and transportation of pistachios and the byproducts is aflatoxin, which can cause irreversible effects on the consumer. Probiotics are one of the most effective and safe methods to reduce aflatoxins. The variables under study were temperature and time, aflatoxin concentration, and probiotic content. In total, 30 treatments were determined through the rotatable central composite design. This is the first and most comprehensive study to optimize the production of probiotic pistachio paste and investigate the detoxification effects of aflatoxin B1 using Bifidobacterium lactis with six treatments and three replications in the pistachio paste matrix. In simple terms, it is possible to remove a higher percentage of toxins by increasing the number of microorganisms and decreasing the toxin level. The highest aflatoxin B1 reduction was observed in pistachio paste with aflatoxin B1 contamination of (19.7039 ng/g), which was spiked with Bifidobacterium lactis (109 CFU/g) and then stored at 25°C for 26.1853 days (aflatoxin B1: 8.00007 ng/g = 59.4% reduction), which is consistent with the permissible limits of the Iran National Standards Organization and the European Commission Regulation. The results showed a significant reduction in the aflatoxin B1 level in pistachio paste. The probiotics reduced aflatoxin B1 contamination to a permissible level. This is an important, safe, and effective solution, and unlike other methods, it increases the nutritional value of the product.